Rint1 inactivation triggers genomic instability, ER stress and autophagy inhibition in the brain - Grigaravičius, Paulius; Kamińska, Ewa; Hübner, C A; McKinnon, P J; Deimling, Andreas von; Frappart, Pierre-Olivier (Cell death and differentiation, 2016)
Endoplasmic reticulum (ER) stress, defective autophagy and genomic instability in the central nervous system are often associated with severe developmental defects and neurodegeneration. Here, we reveal the role played by Rint1 in these different biological pathways to ensure normal development of the central nervous system and to prevent neurodegeneration. We found that inactivation of Rint1 in neuroprogenitors led to death at birth. Depletion of Rint1 caused genomic instability due to chromosome fusion in dividing cells. Furthermore, Rint1 deletion in developing brain promotes the disruption of ER and Cis/Trans Golgi homeostasis in neurons, followed by ER-stress increase. Interestingly, Rint1 deficiency was also associated with the inhibition of the autophagosome clearance. Altogether, our findings highlight the crucial roles of Rint1 in vivo in genomic stability maintenance, as well as in prevention of ER stress and autophagy.
Published online 18 September 2015
Gesehen am 05.08.2020